Hubungan Beban Kerja Perawat Dengan Perilaku Caring Di Instalasi Rawat Inap Ruang Bedah - Rodi Hartawan; Priyanto Priyanto; Imron Rosyidi (Jurnal Kepemimpinan dan Manajemen Keperawatan, 2018)
Workload is a mirror of nursing actions that can be carried out in quantity and quality by a nurse to a person or group of patients who are his/her responsibility. Routine questions that often arise are which patients are treated by which nurse, how many patients can be treated, whether the nurse's burden is maximum or optimum. This study aims to analyze the correlation between nurses' workload and caring behavior at the surgical ward. The design in this study was descriptive correlative with a cross-sectional approach. The population in this study were all nurses of the surgical ward at Ungaran Hospital as many as 30 nurses. Data collection was done by using questionnaires and forms. The data were taken by using purposive sampling technique, the results were analyzed descriptively and statistical tests used  Chi-Square test. The results show nurses with light workload as many as 17 people (56.6%), while those with moderate workload as many as 8 people (26.6%) and those with a heavy workload as many as5 people (16.6%). Nurses with good caring behavior as many as 22 people (73.3%) and nurses with poor caring behavior as many as 8 people (26.7%). From the results of statistical tests with Chi-square test show there is  no correlation between nurse workload and caring behavior, it is known that x2 count = 0.191 <x2 table = 5.991 or based on the probability Asymp-Sig = 0.909> 0.05 (α) then H0 failed to be rejected, so it can be concluded that there is no correlation between nurse workload and caring behavior.